New records of Thambemyia fusariae Capellari, 2015 (Dolichopodidae, Hydrophorinae) from Brazil - Amaral, André; Soares, Matheus Mickael Mota (EntomoBrasilis, 2022)
In this paper, the range of occurrence of Thambemyia fusariae Capellari, 2015 is expanded to south and southeastern Brazil, with the first records for the states of São Paulo and Santa Catarina. These now represent the southernmost records of the species, which has been known only from its type locality in Uruçura, state of Bahia, Brazil. In addition, we provide a distribution map and additional photographs of the species.